Cognitive behavioural therapy for visual hallucinations: an investigation using a single-case experimental design. (27th November 2017) - Thomson, Christina; Wilson, Rea; Collerton, Daniel; Freeston, Mark; Dudley, Robert
Abstract: There has been limited application of cognitive behavioural therapy (CBT) to the treatment of distressing visual hallucinations (VH) in people with psychosis. Preliminary research applying interventions to a novel presenting issue are enhanced by utilizing designs that allow strong inferences to be made about the effect of the intervention. Hence, this study aimed to measure change in appraisal, affect, and behaviour as a consequence of CBT VH, to improve understanding of the process of change. A multiple-baseline experimental single-case design methodology was used with five participants who received a CBT VH treatment package. Participants used daily diary measures to record appraisals, affect, and behaviours related to the distressing VH. Standardized measures were completed at each phase change. Four individuals completed therapy. Formal visual analysis of the data supported by statistical analysis indicated significant changes for appraisal and affect, with replication across three participants. Changes in frequency of VH were reported in two cases. Change was not evident on the standardized measures. This study replicates and extends the findings in showing potential value of CBT VH. Further research should consider alternative methods of capturing behavioural change. Attempts should also be made to replicate across therapists and centres.